Time, Duration and Freedom – Bergson’s Critical Move Against Kant - Kleinherenbrink, Arjen (Diametros, 2014)
Research into Bergson’s philosophy downplays a key development in his first work, Time and free will. It is there that Bergson explicitly opposes himself to Kant by arguing that succession is not a temporal concept, but a spatial one. This is the crucial point of departure for Bergson’s entire philosophy, one that allows him to radically dismiss Kant’s notion of freedom in favor of one based on duration and multiplicity. This text has two aims. Firstly to add to Bergson scholarship by explicating the structure and force of Bergson’s initial argument against Kant, demonstrating that his engagement with Kant is much less incremental than has been suggested in secondary literature. Secondly, to reconstruct the consequences regarding freedom that Bergson immediately draws in departing from Kant, which illustrates the profundity and originality of his thought at the very inception of his oeuvre.